Improving Perioperative Knowledge, Self-Efficacy, and Performance in Labor and Delivery Nurses: A Quality Improvement Project. Issue 4 (July 2019) - Melendez, Christian T.; March, Alice L.; Cunningham, Craig
Abstract : The obstetrical unit utilized a training product (Periop 101: A Core Curriculum OB) to enhance the knowledge, self-efficacy, and performance of nurses circulating for cesarean births. Knowledge was measured using product provided testing. Self-efficacy was assessed using a modified perioperative self-efficacy scale, and performance was evaluated by analyzing documentation accuracy and incident reports. Results demonstrated improvements in perioperative knowledge, self-efficacy, and documentation as well as a reduction in incident reports.